The ALPK1/TIFA/NF-κB axis links a bacterial carcinogen to R-loop-induced replication stress - Bauer, Michael; Nascakova, Zuzana; Mihai, Anca-Irina; Cheng, Phil F; Levesque, Mitchell P; Lampart, Simon; Hurwitz, Robert; Pfannkuch, Lennart; Dobrovolna, Jana; Jacobs, Melanie; Bartfeld, Sina; Dohlman, Anders; et al. (Nature communications, 2020)
Exposure of gastric epithelial cells to the bacterial carcinogen Helicobacter pylori causes DNA double strand breaks. Here, we show that H. pylori-induced DNA damage occurs co-transcriptionally in S-phase cells that activate NF-κB signaling upon innate immune recognition of the lipopolysaccharide biosynthetic intermediate β-ADP-heptose by the ALPK1/TIFA signaling pathway. DNA damage depends on the bi-functional RfaE enzyme and the Cag pathogenicity island of H. pylori, is accompanied by replication fork stalling and can be observed also in primary cells derived from gastric organoids. Importantly, H. pylori-induced replication stress and DNA damage depend on the presence of co-transcriptional RNA/DNA hybrids (R-loops) that form in infected cells during S-phase as a consequence of β-ADP-heptose/ ALPK1/TIFA/NF-κB signaling. H. pylori resides in close proximity to S-phase cells in the gastric mucosa of gastritis patients. Taken together, our results link bacterial infection and NF-κB-driven innate immune responses to R-loop-dependent replication stress and DNA damage.
Keywords: nádory žaludku; reaktivní formy kyslíku; Humans; lipopolysacharidy; Host-Pathogen Interactions; Floxuridine; interakce hostitele a patogenu; Lipopolysaccharides; mutace; adaptorové proteiny signální transdukční; lidé; Adaptor Proteins, Signal Transducing; bakteriální proteiny; Reactive Oxygen Species; Protein Kinases; DNA; DNA Replication; Helicobacter Infections; Helicobacter pylori; replikace DNA; glykosyltransferasy; Glycosyltransferases; nádorové buněčné linie; floxuridin; proteinkinasy; poškození DNA; Bacterial Proteins; DNA Damage; NF-kappa B; Cell Line, Tumor; Mutation; Stomach Neoplasms; infekce vyvolané Helicobacter pylori